Bystander killing effect of DS‐8201a, a novel anti‐human epidermal growth factor receptor 2 antibody–drug conjugate, in tumors with human epidermal growth factor receptor 2 heterogeneity. Issue 7 (22nd June 2016) - Ogitani, Yusuke; Hagihara, Katsunobu; Oitate, Masataka; Naito, Hiroyuki; Agatsuma, Toshinori
Abstract : Antibody–drug conjugates deliver anticancer agents selectively and efficiently to tumor tissue and have significant antitumor efficacy with a wide therapeutic window. DS‐8201a is a human epidermal growth factor receptor 2 (HER2)‐targeting antibody–drug conjugate prepared using a novel linker‐payload system with a potent topoisomerase I inhibitor, exatecan derivative (DX‐8951 derivative, DXd). It was effective against trastuzumab emtansine (T‐DM1)‐insensitive patient‐derived xenograft models with both high and low HER2 expression. In this study, the bystander killing effect of DS‐8201a was evaluated and compared with that of T‐DM1. We confirmed that the payload of DS‐8201a, DXd (1), was highly membrane‐permeable whereas that of T‐DM1, Lys‐SMCC‐DM1, had a low level of permeability. Under a coculture condition of HER2‐positive KPL‐4 cells and negative MDA‐MB‐468 cells in vitro, DS‐8201a killed both cells, whereas T‐DM1 and an antibody–drug conjugate with a low permeable payload, anti‐HER2‐DXd (2), did not. In vivo evaluation was carried out using mice inoculated with a mixture of HER2‐positive NCI‐N87 cells and HER2‐negative MDA‐MB‐468‐Luc cells by using an in vivo imaging system. In vivo, DS‐8201a reduced the luciferase signal of the mice, indicating suppression of the MDA‐MB‐468‐Luc population; however, T‐DM1 and anti‐HER2‐DXd (2) did not. Furthermore, it was confirmed that DS‐8201a was not effective against MDA‐MB‐468‐Luc tumors inoculated at the opposite side of the NCI‐N87 tumor, suggesting that the bystander killing effect of DS‐8201a is observed only in cells neighboring HER2‐positive cells, indicating low concern in terms of systemic toxicity. These results indicated that DS‐8201a has a potent bystander effect due to a highly membrane‐permeable payload and is beneficial in treating tumors with HER2 heterogeneity that are unresponsive to T‐DM1. Abstract : Bystander killing effect of DS‐8201a was evaluated by detecting HER2‐negative cells using an in vivo imaging system. DS‐8201a killed HER2‐negative cells under co‐inoculating condition in both HER2‐positive and negative cells.